(untitled) (JOURNAL OF INNOVATIVE RESEARCH IN MANAGEMENT AND HUMANITIES, 2010)
The study examines the efficacy of capacity-building of basic learning opportunities in stimulating entrepreneurship inventiveness potentials of trainees. Two hypotheses were tested in the study at P < .05 significant level. The first hypothesis examined gender differences in the efficacy of basic learning opportunities in building capacity for inventiveness. The second hypothesis examined the various dimensions of entrepreneurship inventiveness as a result of capacity building of basic learning opportunities. The data for the study was of primary source. A total of 348 University students, with the average age of 23 years, were randomly sampled for the study, from technoscience disciplines, socio-behavioural disciplines, and managerial disciplines. They were challenged to provide answers to a learning exercise that embraced the trio disciplines. With multivariate analyses, it was found out that both genders have above average capacity-building to be inventive. However, the female gender developed more capacity-building to be technically creative, and exhibit social skills inventiveness than the male gender. On the other hand, the male gender had more capacity-building for leadership inventiveness than the female gender. Basically, the value system and motivation could have played significant roles in the outcome. It is therefore recommended that learning opportunities should be open and be encouraged for both genders across disciplines.